The clinical medical librarian's handbook - Stribling, Judy C., 1961- (Medical Library Association books., 2020)
"With contributions by experts working in academic medical centers, Clinical Medical Librarianship provides descriptions of innovative initiatives and programs such as a curriculum for teaching the next generation of medical librarians, recognizing the importance of patient-centered care, and strengthening relationships with clinicians"--